Topics in stochastic processes with special reference to first passage percolation theory - Welsh, JAD (1964)
First passage percolation theory in its most general form is the randomised version of the well-known shortest route problem. It thus has several important physical applications. Ordinary percolation theory is but a special case of this more general problem which we formulate as follows.